Komposisi dan Struktur Gulma pada Fase Vegetatif Padi Sawah (Oryza Sativa L.) di Nagari Singkarak Kabupaten Solok Sumatera Barat - Dera Satria Fitri; Zuhri Syam; - Solfiyeni (Jurnal Biologi Universitas Andalas, 2014)
The study about composition and structure weed of rice field (Oryza sativa L.) in vegetative phase in Singkarak, Solok, West Sumatra was conducted from June to September 2013 by using squares method with purposive sampling plots. The result founded weeds consist of 6 families, 10 species and 5245 individuals. Fimbristylis miliacea showed the highest value of SDR (Summed Dominance Ratio) (36.17%) and the lowest was Hedyotis diffusa (1.61). The diversity index was H'= 1.60 (high). Keywords: Weeds, rice, composition, structure, Phase